Citizen science, the body of Christ, and testimonial epistemology: toward a distributed theology - Friedrich, Benedikt; Reichel, Hanna; Renkert, Thomas (The ecumenical review, 2020)
How does explicit theological knowledge emerge out of communal practices, who is involved in its production, and what are its procedures? These are neither neutral nor arbitrary methodological questions; they are themselves deeply theological. Digital innovations and the subsequent transformations of society and academia invite us to redefine the work of theology. Epistemologically drawing on a theology of the cross and centring the communal nature and vulnerable existence of the witnessing community, we develop a model of doing theology that is collaborative and exploratory within the medial transformations of the digital age. Taking cues from participatory research conceptions of “citizen science,” we propose going toward and beyond a “citizen theology.” We need the courage to conceive of a theology that is ultimately centreless. Therefore, we cannot aspire to testimonially responsible forms of doing theology without striving for epistemic justice and diaconal empowerment at a global level. The “distributed theology” we envision promotes global (catholic), decentral (apostolic), and communal (local) forms of knowledge production by the whole of the body of Christ in ever more distributed ways.
First published: 23 April 2020
Gesehen am 16.11.2021